DIDACTIC-PEDAGOGICAL PROPOSITIONS AND ITS PROJECTIONS TO PHYSICAL EDUCATION TEACHING - Bolzan, Erica; Santos, Wagner dos (Journal of Physical Education (Maringá), 2015)
Analyzes didactic-pedagogic propositions published by the StateDepartment of Education, with the aim of investigating its forms and protocolsfor designing pedagogical practices of Physical Education. It is characterizedas a documental research that used as sources: Curricular Proposal of MinasGerais, the Basic Curriculum of Espírito Santo, the Curriculum Debate in Goiás,the Theoretical and Methodological Orientations of Pernambuco, the PublicTextbook of Paraná, the Teacher’s Notebooks of São Paulo and Didactic Materialsof Rio de Janeiro. The documents were classified as teaching collections, whendiscussing theoretical presupposition to the curriculum, or as boxes of utensilswhen prescribing teaching possibilities. The sources are the product of apartnership between universities and educational institutions, constructed indialogue with teachers of networks. The shapes of the documents indicaterelationship with current national policy of basic education by the principlesof integralization, interdisciplinarity and curriculum organization in areas ofknowledge.